2013
DOI: 10.1186/1471-2148-13-209
|View full text |Cite
|
Sign up to set email alerts
|

Horizontally acquired divergent O-antigen contributes to escape from cross-immunity in the classical bordetellae

Abstract: BackgroundHorizontal gene transfer (HGT) allows for rapid spread of genetic material between species, increasing genetic and phenotypic diversity. Although HGT contributes to adaptation and is widespread in many bacteria, others show little HGT. This study builds on previous work to analyze the evolutionary mechanisms contributing to variation within the locus encoding a prominent antigen of the classical bordetellae.ResultsWe observed amongst classical bordetellae discrete regions of the lipopolysaccharide O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…They may also have been associated with hybridization at the margin of the range of previously geographical isolated species [9598]. One possible scenario to account for the formation of the contact zone between L .…”
Section: Discussionmentioning
confidence: 99%
“…They may also have been associated with hybridization at the margin of the range of previously geographical isolated species [9598]. One possible scenario to account for the formation of the contact zone between L .…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of a hydrophobic moiety called lipid A (encoded by the lpx locus in Bordetella), an oligosaccharide core and a long serospecific polysaccharide called the O antigen [38]. B. pertussis lacks the wbm operon [39] and does not produce this O antigen [40], hence the name LOS rather than LPS.…”
Section: The B Pertussis Los Endotoxinmentioning
confidence: 99%
“…14 Hester and co-workers suggested that horizontally acquired divergent O-antigen contributes to escape from cross-immunity in the classical Bordetellae. 15 Dispersal position of these genes may suggest a possible source of LPS structure diversity between different Bordetella circulating strains. However, when other available genomes were analyzed, those genes were in the same relative position suggesting that glycosyltransferase genes are part of the core rather than accessory genome.…”
Section: Lipopolysaccharide Bordetella Glycosyltransferase a B S T R mentioning
confidence: 99%